Sustainability Evaluation of Biodiesel from Arthrospira platensis and Chlorella vulgaris under Mixotrophic Conditions and Salinity Stress - Martins, António A. (2017)
This study performs a sustainability evaluation of biodiesel production from microalgae Arthrospira platensis (A. platensis) and Chlorella vulgaris (C. vulgaris) cultivated in mixotrophic conditions, with and without salinity stress, in comparison to autotrophic conditions. The life cycle steps considered for the evaluation are microalgae cultivation, biomass harvesting, lipids extraction, biodiesel production, distribution and use. Three sustainability indicators (LCEE – Life Cycle Energy Efficiency, FER – Fossil Energy Ratio and GW – Global Warming) are calculated based on laboratory experiments conducted in this study and literature data to complement inventory data, thus allowing a more truthful and accurate sustainability evaluation. Results show that in the current conditions, production of biodiesel from these microalgae is not energy efficient, since LCEE and FER values are lower than one, except for C. Vulgaris at mixotrophic growth, without salinity stress. GW values are always positive, meaning that carbon captured during microalgae growth does not compensate the carbon emitted in the whole process. A comparative analysis of the various process steps is also conducted, showing that the water removal and lipids recovery are critical steps for the process sustainability. One possible solution is to explore these microalgae in a biorefinery process, where the desired product is obtained along with a host of by-products, increasing the process sustainability and competitiveness.